Identification of Phthalates, Methyl Esters and Siloxanes through GCMS analysis, biological investigation, DFT and Molecular Docking studies on Methanolic Subfractions of Hibiscus Rosa Sinensis flower extract - Farah Yasmin, Zill-I-Huma Nazli, Nusrat Shafiq, Maryam Aslam, (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: Plants are vital source of bioactive molecules, so they play a significant role in prevention and curing of various health disorders. The Hibiscus rosa sinensis, an ornate with attractive flowers, has conventionally been utilized globally as a curative agent for a wide range of ailments. Methods: In current study, we prepared crude methanolic extract of flowers of Hibiscus rosa sinensis and subjected that to in vitro biological evaluation to assess its antidiabetic and antioxidant potential. Outcomes of in vitro evaluation confirmed the excellent antidiabetic and antioxidant potency of Hibiscus flowers. Further crude methanolic extract was fractionated to hexane, ethyl acetate and methanol fractions. Among the three fractions, we subjected methanolic fraction to GCMS analysis to explore the bioactive molecules contained by this fraction. Results: The spectral data obtained from GCMS analysis revealed the existence of a total of 12 compounds including phthalates, methyl esters and siloxanes which are known to have a range of reported pharmacological activities. Successively, we subjected the identified molecules to molecular docking to assess their antidiabetic and antioxidant potential and DFT study to explore the reactivity of their molecular structures. As far as we are aware, it is the first report on the in-silico antidiabetic (128.1µM) and antioxidant (410.0µM) potential assessment of phytoconstituents of methanolic extract of floral part of Hibiscus rosa sinensis. The results revealed the H. Sinensis plat as more viable and good alternative to existing natural remedies. Molecular docking analysis pointed out four potential antidiabetic molecules, Di (3E,5E)-hepta-3,5-dien-1-yl) phthalate (2), 1H,15H-Hexadecamethyloctasiloxane (5), Hexakis (trimethylsiloxy) disiloxane(11) and Tetracosamethylcyclododecasiloxane(12) that displayed excellent binding affinity against receptor proteins, 3BAJ and 1HNY even higher than the reference compound Acarbose. However, all identified compounds except Octadecamethylnonasiloxane (5) and Cyclodecasiloxane, eicosamethyl-(6) exhibited promising affinity for antioxidantproteins, 2I3Y and 1XAN. Moreover, the molecule Tetracosamethylcyclododecasiloxane(12) was explored as lead compound among the identified molecules as it showed strongest interaction with all interacting proteins i.e.-156.997Kcal/mol, -179.446 Kcal/mol, -155.979 Kcal/mol, -193.859 Kcal/mol for 3BAJ, 1HNY, 2I3Y and 1XAN, respectively. Conclusion: The findings of our study help us to conclude that conventionally utilizeted Hibiscus rosa sinensis flowers and its identified molecules from the methanolic extract possess excellent antioxidant and antidiabetic potential. Keywords: GCMS analysis, DFT, Molecular Docking, Antidiabetic, Antioxidant